2016
DOI: 10.1002/mar.20970
|View full text |Cite
|
Sign up to set email alerts
|

Communicating a Key Benefit Claim Creatively and Effectively through Five Conveyor Properties

Abstract: In today's clutter of marketing communications, creative advertisements are capable of grabbing the viewers’ attention with the aim of conveying the product's key benefit claim (KBC). A proven technique for drawing attention to an ad and communicating a KBC is the use of a “remote conveyor” that is seemingly unrelated to the product (e.g., a dolphin and a sports watch for conveying its waterproofness). Drawing on associative memory theory, this article investigates the potentially antagonistic relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…For example, the use of analogy has been found to be effective (Madrigal and King 2017) and so has metaphor, but irony has been shown to have a negative effect on ad evaluation and little to no effect on persuasiveness (Burgers et al 2015). Some argue for a focus on products' "key benefit claim" (Althuizen 2017). In addition, it has been found that consumers are able to assess the expense and effort involved in creative work and both are positively correlated to attitudes toward the brand (Modig, Dahlén and Colliander 2014).…”
Section: Identifying Creative Executional Factors and Measuring Theirmentioning
confidence: 99%
“…For example, the use of analogy has been found to be effective (Madrigal and King 2017) and so has metaphor, but irony has been shown to have a negative effect on ad evaluation and little to no effect on persuasiveness (Burgers et al 2015). Some argue for a focus on products' "key benefit claim" (Althuizen 2017). In addition, it has been found that consumers are able to assess the expense and effort involved in creative work and both are positively correlated to attitudes toward the brand (Modig, Dahlén and Colliander 2014).…”
Section: Identifying Creative Executional Factors and Measuring Theirmentioning
confidence: 99%
“…What is meant is to avoid discussions that are out of the scientific context and extend to things that are not the substance of the learning. A teacher also needs to convey knowledge creatively and in a fun way but avoid conveying things that are unnecessary and unrelated to the subject matter (Althuizen, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, by combining research on marketing communications using rhetoric devices and concentrating on the creative text descriptions in general, our claims integrate and extend other studies of creative marketing messages to the descriptions of products that appear online. This is a novel and necessary extension of the literature on traditional advertisements (Althuizen, 2017;Dahlén et al, 2018) given the prevalence of e-commerce today. This paper also identifies a moderator (i.e., construal level) that is more applicable to an online context, thus expanding and enriching the literature.…”
Section: Theoretical Implicationsmentioning
confidence: 96%
“…Recent research has found that abstract mindsets help recipients to process metaphors in health communication (Landau et al, 2019 ). A creative text description in this research contains more rhetoric devices with figurative language using analogies such as metaphors and personification (Ang and Low, 2000 ; Dahlén et al, 2008 ; West et al, 2019 ), which means claiming product's key benefits with “remote conveyors” that are seemingly unrelated to the product (Althuizen, 2017 ). More precisely, for example, in the Supplementary Material , “female treasure” has been used to depict the shea butter's superior advantage while the two objects have different surface attributes.…”
Section: Theory and Hypothesesmentioning
confidence: 99%